RANCANGAN ANTARMUKA UNTUK KALIBRASI SENSOR SISTEM TELEMETRI KUALITAS AIR KOLAM BUDIDAYA IKAN - Subandri, Muhammad Asep; Fajri P. Putra; Rahmat Fajrul (Politeknik Negeri Bengkalis, 2023)
This research aims to develop a calibration interface that enables the routine and effective calibration of water quality telemetry system sensors in fish cultivation ponds. This interface is designed to provide users, namely fish farmers, the ability to perform dynamic calibration based on linear regression methods. With this feature, fish farmers can recalibrate the sensor based on fluctuations in the cultivation pond environment, thereby improving measurement accuracy continuously. The calibration method employed is linear regression, which allows for the identification of the mathematical relationship between sensor data and reference data. By collecting sensor data and reference data, linear regression parameters such as offset and slope can be calculated and applied to sensor measurements. This calibration interface feature can be accessed through a computer or mobile device with an intuitive display, making it easy for fish farmers to operate. The research results indicate that the use of a dynamic calibration interface with linear regression methods can enhance sensor measurement accuracy continuously. Fish farmers can perform routine calibrations in accordance with environmental changes, contributing to better water quality management in fish cultivation. The success of this interface opens opportunities for the development of technology that supports optimal fish growth and health within the environment.